AGEING WITH A LEARNING DISABILITY: A CRITICAL LITERATURE REVIEW. (11th November 2018) - Victor, C; Williams, V; Kinnear, D; Ryan, S
Abstract: In the United Kingdom, there are an estimated 1.14 million people with a learning disability. Little is known about the experiences of this group of people as they age and how they conceptualise 'successful ageing'. We undertook a systematic literature review of the experience of ageing for adults with a learning disability and identified 65 papers published between 2001 and 2016 categorised into 6 domains health; activities of daily living and function; experiences of ageing; quality of life and well-being; autonomy and transitions. Most papers, 43, focused upon health/activities of daily living with 11 studies examining ideas about ageing, autonomy and transitions highlighted the lack of research looking at social inclusion and engagement social exclusion. We still lack a clear understanding as to what a good later life for older learning disabled people consists of and how, if at all, it differs from the rest of the population.